On business education in Singapore: The past, the present and the future - TAN, Teck Meng (Institutional Knowledge at Singapore Management University, 1999)
Examines the developments in business education in Singapore and directions for its development. Post-graduate programs; Status of management education at universities; Broadening of education in Singapore universities.